Corporate Governance and Macroeconomics on The Financial Stability of Islamic Banks - Siti Rahmayuni; Ardi Paminto (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study discusses the influence of Corporate Governance and macroeconomics on financial stability in the Islamic banking sector. Design/methodology/approach: This study employed a quantitative and Data analysis uses panel data regression. Findings: while the independent variable in this study is Corporate Governance and Macroeconomics, with the results showing that Corporate Governance and macroeconomics have no partial effect.. Research limitations/implications: There are only two variables considered in this paper: corporate governance and macroeconomic. Practical implications: partially corporate governance has no effect and macroeconomics has a negative effect. Originality/value: TThis study calculates and finds out the truth of corporate governance and macroeconomic variables on financial stability. Paper type: Research Paper Keyword: Corporate Governance, Macroeconomics, Financial Stability, Inflation